Health care variation: time to act. (21st November 2016) - Buchan, Heather A; Duggan, Anne; Hargreaves, Jenny; Scott, Ian A; Slawomirski, Luke
Summary: Geographic variation in health care use has been demonstrated in many countries over many years. Such variation can be warranted — in response to patient need or preference for care — or unwarranted. Unwarranted variation raises concerns about equity and appropriateness of care. Recent analyses of health care provision in the Australian atlas of healthcare variation show that when routinely available Australian data are mapped by residence of patient, there are wide variations in rates of use of diagnostic tests, dispensing of prescriptions for a range of indications, surgical procedures and hospital admission rates. Despite the wealth of studies demonstrating variation in care internationally, there is relatively little research that explores the best ways of responding to unwarranted variation. Recommendations for action in the Australian Atlas focus on some approaches that could be used in Australia.